Reactivity and Selectivity of Boron-Substituted Alkenes in the Diels-Alder Reaction with Cyclopentadiene. A Study of the Electron Charge Density and Its Laplacian - Vallejos, Margarita (2014)
The effect of the nature of the boron moiety upon the reactivity and the selectivity of a variety of vinylboron dienophiles (1−12) in the Diels−Alder (DA) reaction was investigated using density functional theory and the quantum theory of atoms in molecules. The calculated reactivity of the dienophiles decreases in the order vinylborane (1) > dihalovinylboranes (2−4) > dialkylvinylboranes (5−7) ≈ vinyl boronic acid (8) > vinylboronates (9, 10) > vinyl MIDA boronate (11) ≈ vinyltrifluoroborate (12). The DA reactions of 1−7 were slightly endo-selective due to the stronger C6−B secondary orbital interaction in the endo transition structures (TSs) evaluated by the C6|B delocalization index. In the TSs of 5 and 7, a combination of electronic and steric factors reduce the endo selectivity. The moderate exo selectivity calculated for the DA reactions of boronates 8−11 was attributed mainly to the hydrogen bond between the oxygen atom of boronate moieties and one of the acidic hydrogens of the methylene of cyclopentadiene in the exo TSs, which also reduces the ability of the oxygen lone pairs to donate electron density into the vacant boron orbital. Interestingly, the cooperative effect between the two hydrogen bonds in the exo TS of the DA reaction of vinyltrifluoroborate (12) determines the almost exclusive exo selectivity predicted for this DA reaction. We propose that the relative reactivities of the dienophiles can be estimated by the charge density (ρr) and its Laplacian (∇2 ρr) at the (3,+1) critical point in the topology of ∇2 ρr, evaluated at the reactant molecules in the ground state. The profiles of the several topological parameters along the reaction are affected by the nature of the substituents attached to the boron atom and by the mode of addition (endo and exo) in the DA reactions.